Effective intraocular pressure management and vision preservation in secondary glaucoma associated with carotid-cavernous fistula: A case report (Indian Journal of Case Reports, 2026)
Carotid-cavernous fistulas (CCFs) are abnormal arteriovenous connections between the cavernous sinus and branches of the internal or external carotid arteries. Although uncommon, CCFs are an important cause of secondary glaucoma due to increased episcleral venous pressure, and they present significant diagnostic and therapeutic challenges. Uncontrolled intraocular pressure (IOP) can lead to irreversible blindness, highlighting the urgency of timely and effective management. We report the case of a 65-year-old woman with a history of hypertension and dyslipidemia who presented with persisting bilateral redness and dry sensation in both eyes (BE), along with visual decline, leftsided proptosis, conjunctival injection (more severe in the left eye [LE]), and a palpable bruit. IOP was elevated in the LE despite maximal topical therapy. Imaging with computed tomography angiography and digital subtraction angiography confirmed a Type C CCF. This case highlights the importance of addressing the underlying cause of secondary glaucoma, as maximal anti-glaucoma medications alone may be insufficient if the primary pathology remains unresolved.